FATE IN THE FOREST: STRUCTURALIST READINGS OF MYTHEME, TOTEMISM, AND BINARY OPPOSITIONS IN BLOOD WEDDING (Al-Aasar, 2025)
Informed by the principles of structuralist anthropology, this paper offers a re-reading of Federico García Lorca’s Blood Wedding as a modern myth inscribed with rich symbolic codes and ritualistic undercurrents. Through the prism of Claude Lévi-Strauss’s structuralist framework, Blood Wedding emerges as a matrix of binary tensions—masculinity and femininity, instinct and repression, life and death, nature and culture—each shaping the ideological scaffolding of the narrative. Figures such as the moon, horse, beggar woman, knives, and forest function as mythemes—cultural signifiers that reactivate archaic sacrificial logics and ancestral codes. These elements unravel the deeper structures behind social constructs such as honor, marriage, and familial duty. The presence of nonhuman entities imbues the narrative with totemic resonance, evoking a premodern cosmology in which human volition is subordinated to cyclical inevitabilities. By unsettling realist conventions, Blood Wedding reanimates the primordial purpose of theatre as a mythic apparatus through which cultural anxieties, ancestral memory, and ritualized violence are inscribed and preserved.